REKONSTRUKSI PERKARA SEBAGAI UPAYA DALAM MENGUNGKAP KEJAHATAN - Sri Yuliana (Legalita, 2022)
In essence, law enforcement is a process of adjustment between values, rules and real behavior patterns that aim to achieve peace, so that the main task of law enforcement itself is actually an effort, activity or work so that the law is upright and peace is maintained. stand up. In order to achieve this goal, there must be an adjustment between values ​​or rules and the real behavior faced by law enforcers. Law enforcement, which is a process of concretizing an abstract form of law into a concrete one, means that laws and regulations are meaningless if they are not applied concretely by law enforcement officials. In law enforcement itself, it is necessary to have evidence activities that can be used by law enforcers (investigators) in this case to take other actions, including reconstructing. In this case, the police in carrying out law enforcement use their coercive power to obtain clear evidence that is in accordance with law enforcement when viewed from the point of view of the subject, law enforcement can be carried out by a broad subject and can also be interpreted as law enforcement efforts that involve all subjects. law in every legal relationship. In a narrow sense, in terms of the subject matter, law enforcement is only defined as the efforts of certain law enforcement officials to guarantee and ensure that the law is enforced, if necessary, law enforcement officials are allowed to use force. Law enforcement efforts are divided into two, namely by penal (criminal law) and non-penal (outside criminal law). In this case, reconstruction is included in the penal method, namely to enforce the law for the victim so that the incident that caused harm to the victim can be revealed so that the real incident is clear. This also applies to law enforcement against suspects, meaning that in the reconstruction the suspect needs to be proven whether it is true that the suspect committed the crime or not. The implementation of reconstruction or other activities carried out by police investigators must have the basis of the laws and regulations governing it. Without the rules that regulate it, it can be said that law enforcers themselves do not enforce the law, even against the law.